Evaluation of nuclear quadrupole interactions as a source of magnetic anisotropy in the radical pair model of the avian magnetic compass - Efimova, O; Hore, P (2009)
One of the principal proposed biophysical mechanisms put forward to explain the avian magnetic compass sense centres around magnetically sensitive chemistry. Based on a large number of in vitro studies of the effects of applied magnetic fields on the yields and rates of chemical reactions it has been suggested that the anisotropic magnetic interactions in spin-correlated radical pairs could be the source of the directional information that allows migratory birds to use the Earth's magnetic field as a navigational aid. Here numerical quantum mechanical simulations are employed to explore the possibility that the hitherto neglected nuclear quadrupole interaction may provide directional information in a radical pair magnetoreceptor. It is concluded that although nuclear quadrupole interactions could fulfil this function, they are unlikely to influence significantly the reaction yield anisotropy in the flavin-tryptophan radical pair that has been proposed as the in vivo magnetoreceptor.